2011
DOI: 10.1093/humrep/der025
|View full text |Cite
|
Sign up to set email alerts
|

microRNAs expression in endometriosis and their relation to angiogenic factors

Abstract: Expression levels of miRNAs related to angiogenesis were different in eutopic endometrium from that observed in ovarian endometrioma. This could influence the expression of angiogenic factors and play a role in the pathogenesis of endometriosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
42
2
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(51 citation statements)
references
References 41 publications
5
42
2
2
Order By: Relevance
“…For example, the miR-200 family has been reported to be highly expressed in EEC compared with normal endometrial tissues and may play an important role in cancer growth (17). In uterine disorders, miR-21 has been found to be associated with endometriosis, leiomyoma and cervical cancer (18,19). However, the exact role of miR-21 in EEC is not fully understood.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the miR-200 family has been reported to be highly expressed in EEC compared with normal endometrial tissues and may play an important role in cancer growth (17). In uterine disorders, miR-21 has been found to be associated with endometriosis, leiomyoma and cervical cancer (18,19). However, the exact role of miR-21 in EEC is not fully understood.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9] In human endometrium, several studies, including next generation sequencing have identified the expression of a large number of miRNAs, some of which showed altered expression in endometriosis and endometrial cancer. [10][11][12][13][14][15][16][17] Among those altered in endometriosis and endometrial cancer, include the members of miR-200 family: miR-200c/141 and miR-200b/200a/429 clusters. 11,13,15,[18][19][20][21][22] The expression and function of miR-200 family has been well documented in various tissues and cells, where they target the expression of many genes, including ZEBs, the transcription factors that regulate cellular transformation, more specifically epithelial-to-mesenchymal transition (EMT) during cancer development and progression through repression of adhesion molecules such as E-cadherin.…”
Section: Introductionmentioning
confidence: 99%
“…Takehara et al 32 have reported an increase in VEGF mRNA expression in endometriotic tissue (early stages) compared with the eutopic endometrium. However, in some previous reports, the authors found that ovarian endometriomas had lower VEGF levels and higher TSP-1 levels compared to eutopic endometrium or peritoneal lesions [9][10][11] and thought that 3 clinically distinct lesions of endometriosis, including peritoneal lesion, ovarian endometrioma, and deep infiltrating endometriosis, may be variants of the same pathologic process, or they may be caused by different mechanisms. 22,33 In the present study, we did not detect any increase in VEGF levels or any decrease in TSP-1 in ovarian endometrioma and even found a lower VEGF level and a higher TSP-1 level in comparison with ovarian tissues surrounding the mature teratoma that is a benign tumor without the capabilities of invasiveness and metastasis.…”
Section: Discussionmentioning
confidence: 93%
“…However, in some published reports, the authors found that ovarian endometriomas had lower levels of VEGF and higher levels of TSP-1 compared to eutopic endometrium or peritoneal lesions. [9][10][11] If so, how does this condition initiate and develop with low capabilities of angiogenesis and metastasis?…”
Section: Introductionmentioning
confidence: 99%